ESC‐sEVs Rejuvenate Senescent Hippocampal NSCs by Activating Lysosomes to Improve Cognitive Dysfunction in Vascular Dementia. Issue 10 (20th March 2020) - Hu, Guowen; Xia, Yuguo; Zhang, Juntao; Chen, Yu; Yuan, Ji; Niu, Xin; Zhao, Bizeng; Li, Qing; Wang, Yang; Deng, Zhifeng
Abstract: Vascular dementia (VD) is one of the most common types of dementia, however, the intrinsic mechanism is unclear and there is still lack of effective medications. In this study, the VD rats exhibit a progressive cognitive impairment, as well as a time‐related increasing in hippocampal neural stem cells (H‐NSCs) senescence, lost and neurogenesis decline. Then, embryonic stem cell‐derived small extracellular vesicles (ESC‐sEVs) are intravenously injected into VD rats. ESC‐sEVs treatment significantly alleviates H‐NSCs senescence, recovers compromised proliferation and neuron differentiation capacity, and reverses cognitive impairment. By microarray analysis and RT‐qPCR it is identified that several miRNAs including miR‐17‐5p, miR‐18a‐5p, miR‐21‐5p, miR‐29a‐3p, and let‐7a‐5p, that can inhibit mTORC1 activation, exist in ESC‐sEVs. ESC‐sEVs rejuvenate H‐NSCs senescence partly by transferring these miRNAs to inhibit mTORC1 activation, promote transcription factor EB (TFEB) nuclear translocation and lysosome resumption. Taken together, these data indicate that H‐NSCs senescence cause cell depletion, neurogenesis reduction, and cognitive impairment in VD. ESC‐sEVs treatment ameliorates H‐NSCs senescence by inhibiting mTORC1 activation, and promoting TFEB nuclear translocation and lysosome resumption, thereby reversing senescence‐related neurogenesis dysfunction and cognitive impairment in VD. The application of ESC‐sEVs may be a novel cell‐free therapeutic tool for patients with VD, as well as other aging‐related diseases. Abstract : Hippocampal neural stem cells (H‐NSCs) senescence causes their loss and neurogenesis decline, resulting in cognitive impairment in vascular dementia (VD). Embryonic stem cells derived small extracellular vesicles (ESC‐sEVs) can rejuvenate H‐NSCs senescence by transferring miRNAs including miR‐17‐5p, miR‐18a‐5p, miR‐21‐5p, miR‐29a‐3p, and let‐7a‐5p to inhibit mTORC1 activation, and promote transcription factor EB nuclear translocation and lysosome resumption, which reverses senescence‐related neurogenesis dysfunction and cognitive impairment in VD.